Correlation between mechanical properties and microstructure of different aluminum wire qualities after ultrasonic bonding. Issue 9 (August 2015) - Broll, M.S.; Geissler, U.; Höfer, J.; Schmitz, S.; Wittler, O.; Schneider-Ramelow, M.; Lang, K.D.
Abstract: Three different heavy aluminum wire qualities were investigated regarding their microstructural evolution after ultrasonic bonding by electron backscatter diffraction and nanoindentation. The results complete the findings of our recent research regarding the effect of bonding mechanisms on the wire bond microstructure and its local mechanical properties. Local elastic-plastic material parameters of the bonded wires were approximated on the basis of the elastic anisotropy of crystals and a correlation between hardness and stress. Highlights: The microstructural evolution of different Al-wires after wire bonding was studied. All investigated wires exhibit a rotated cube textured area after wire bonding. The RC textured area exhibit the lowest hardness within wedge. Elastic material properties of the as-received and bonded wires were calculated. Plastic properties were determined through the correlation of hardness and stress.